2003
DOI: 10.1046/j.1365-2672.2003.01937.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tetracycline exposure on tetracycline resistance and the carriage of tetracycline resistance genes within commensal Escherichia coli populations

Abstract: Aims: To assess the influence of incremental tetracycline exposure on the genetic basis of tetracycline resistance within faecal Escherichia coli. Methods and Results: Through the adoption of a novel combination of multiple breakpoint selection, phenotypic characterization and the application of a polymerase chain reaction based gene identification system it proved possible to monitor the influence of antibiotic exposure on resistance gene possession. Using tetracycline as a case study a clear hierarchy was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
53
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 32 publications
9
53
1
1
Order By: Relevance
“…The E. coli isolates assessed in this study displayed similar levels of resistance to tetracyclines, ampicillin, gentamicin and fluoroquinolones as were previously reported for E. coli strains isolated from diseased swine in China by Tian et al (2009). High levels of resistance to tetracycline (~60-95%) have also been detected in E. coli isolates recovered from apparently healthy swine on-farm or at slaughter in other countries (Kozak et al, 2003;KijimaTanaka et al, 2003;Teshager et al, 2000;Blake et al, 2003). Most of E. coli isolates (67.3%) from swine were resistant to fluoroquinolones (e.g.…”
Section: Et Al 1581supporting
confidence: 81%
“…The E. coli isolates assessed in this study displayed similar levels of resistance to tetracyclines, ampicillin, gentamicin and fluoroquinolones as were previously reported for E. coli strains isolated from diseased swine in China by Tian et al (2009). High levels of resistance to tetracycline (~60-95%) have also been detected in E. coli isolates recovered from apparently healthy swine on-farm or at slaughter in other countries (Kozak et al, 2003;KijimaTanaka et al, 2003;Teshager et al, 2000;Blake et al, 2003). Most of E. coli isolates (67.3%) from swine were resistant to fluoroquinolones (e.g.…”
Section: Et Al 1581supporting
confidence: 81%
“…Several investigations have studied tetracycline resistance in bacteria by examining their ability to grow in the presence of drugs, but these studies are not useful for determining the types of tetracycline resistance determinants responsible for antibiotic resistance in bacteria (7). On the Other hand, molecular microbiology techniques can accurately describe genetic basis of antibiotic resistance in bacteria (18).…”
Section: Discussionmentioning
confidence: 99%
“…Karami et al [21] reported that Tc r is an attractive model for studying the ecology of antibiotic resistance. Tc r determinants were detected from different bacteria isolated from different environmental samples [22][23][24]. On the other hand, Al-Bahry et al [5] used molecular techniques for detection of Amp resistant determinants for biomonitoring of marine habitats using multiplex PCR.…”
Section: Discussionmentioning
confidence: 99%